Million-dollar throw - Lupica, Mike (Puffin Books, 2010)
Eighth-grade star quarterback Nate Brodie's family is feeling the stress of the troubled economy, and Nate is frantic because his best friend Abby is going blind, so when he gets a chance to win a million dollars if he can complete a pass during the halftime of a New England Patriot's game, he is nearly overwhelmed by the pressure to succeed.